Innovative Bread Filling from Saba Banana Peel Pulp: Integrating Waste Management and Sustainability - Cahyadi Wijaya, I Nyoman; Bulkaini, Lukman Ahmadi; Seçuk, Berkay (Politeknik Pariwisata Lombok, 2025)
Introduction:The growing concern for environmental sustainability and waste management necessitates innovative solutions to reduce food waste. The saba banana peel, often discarded, is rich in nutrients and can be repurposed into valuable food products. This research explores the feasibility of repurposing saba banana peel pulp into bread fillings, focusing on organoleptic properties and consumer acceptance. Methodology:An experimental and descriptive research design was employed, testing formulations with varying concentrations of banana peel pulp percentage into 3 categories, 30%, 60%, and 100%. Various formulations were created and subjected to organoleptic testing by a panel of 30 participants. The sensory attributes evaluated included taste, texture, aroma, and visual appeal. Additionally, the environmental impact of using saba banana peel pulp was assessed by comparing waste reduction before and after its application. Findings:The findings revealed that bread fillings incorporating saba banana peel pulp received favorable ratings, particularly for taste and texture. The highest-rated formulation achieved significant acceptance across all sensory attributes. The study also demonstrated a 20% reduction in waste, emphasizing the potential of saba banana peel pulp to enhance food sustainability and waste management practices. Conclusion:The findings highlight the dual benefits of enhancing food product diversity and promoting environmental sustainability through effective waste management. Future research should explore the scalability of this approach in the food industry.